Suicide Ideation and Social Support Trajectories in National Guard and Reserve Servicemembers. Issue 3 (3rd July 2022) - Wang, Jing; Ursano, Robert J.; Gifford, Robert K.; Dinh, Hieu; Weinberg, Alysse; Cohen, Gregory H.; Sampson, Laura; Galea, Sandro; Fullerton, Carol S.
Abstract : Objective : Since 2004 increased rates of suicide have been noted in the US Armed Forces. We examined the association of social support (SS) trajectories and suicide ideation (SI) over a four-year period in Reserve Component (RC) servicemembers (National Guard and Reserve). We also examined baseline mental health measures, as predictors of the identified trajectories. Methods : Structured interviews were conducted with a nationally representative sample of 1, 582 RC servicemembers at baseline and three follow-up waves. Latent growth mixture modeling identified SS trajectories and the association with follow-up SI. Multinomial logistic regression analyses were used to predict SS trajectories using baseline measures of demographics and mental health. Results : We identified four trajectories of SS and their associated prevalence of follow-up SI: low (n = 60, 3.8%; SI = 30.5%), medium (n = 229, 14.5%; SI = 14.1%), high–low (n = 66, 4.2%; SI = 13.6%), and high–high (n = 1, 227, 77.5%; SI = 4.2%). There were significant differences in follow-up SI prevalence between each pair of SS trajectories except between the medium-SS and high-low-SS trajectories. Baseline SI, post-traumatic stress disorder (PTSD), depression, binge drinking, and mental health diagnosis were associated with increased likelihood of being on a low-SS or medium-SS trajectory. Baseline PTSD discriminated being on the high-high-SS and high-low-SS trajectories. Conclusion : Results support four trajectories of social support and that individuals with low or decreasing SS are likely to have greater follow-up SI. Baseline mental health assessments can identify these risk trajectories.